The Effectiveness of Satreskrim Performance in Disclosing Criminal Offenses of Theft in the Jurisdiction of the Kediri City Police - Dewanto, Yogatama Parikesit Poetra (Police Studies Review, 2024)
The number of curanmor cases in the Kediri City Police area during 2020-2023 (January-August) showed a fairly high number and tended to increase even though in 2021 it had decreased. There is still a considerable difference between the number of curanmor cases that occur and the curanmor cases that can be resolved, which is one indicator that the performance of the Kediri City Police Satreskrim in disclosing curanmor cases is still not effective. Based on Police Regulation Number 2 of 2021 in Article 33 paragraph (1), Satreskrim has the role of handling various issues related to crime or criminal acts. Therefore, a study was conducted that aims to determine and analyse the organisational resources and performance effectiveness of Satreskrim in disclosing the crime of curanmor in the Kediri City Police jurisdiction. The theory that the author uses in this research is management theory and organisational resource theory by George R. Terry. While the concepts used include: the concept of effectiveness, the concept of theft of motorised vehicles, and the concept of performance. The theory is used as the basis of this research.The approach used by the author in this research is a qualitative approach with the focus of research in the form of the effectiveness of the performance of the Kediri City Criminal Investigation Unit in uncovering criminal acts of curanmor. The data sources used are primary and secondary data sources. The data collection techniques used in this research are interviews, observations and document studies.